Meteorological data from Erssjön, Floating platform - Skogaryd Research Catchment (University of Gothenburg, 2025)
Automatic weather station data from locations within the distributed Swedish research infrastructure SITES. Check preview or file for the specific parameters included at this location. Data has been quality controlled and cleaned from outliers and other events producing unrealistic data. Gaps have not been filled.
Skogaryd Research Catchment (2025). Meteorological data from Erssjön, Floating platform, 2024 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/9tNJ7aaPkgcViNo01F02g0P0
Keywords: Skogaryd Research Catchment; Atmospheric radiation; Humidity; Precipitation; Surface Winds; Time instant; Time instant; Air temperature; Air temperature; Relative humidity; Relative humidity; Photosynthetically active radiation; Photosynthetically active radiation; Wind speed; Wind speed; Wind direction; Wind direction; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap